The potential of blockchain technologies for digital marketing – A critical assessment - Michail Vafeias; Nektarios Sartzetakis (Institute of Computer Science (IOCS), 2023)
Blockchain is an emerging technology that is already finding applications in various sectors of economy, governance and trade, due to its attractive features of transparency and auditability. Digital marketing and advertising, i.e., the promotion of goods and services via digital media is currently a multibillion-dollar market with an increasing growth rate and crucial to the global economy. The potential of blockchain technologies for digital marketing applications has been recognized the last few years by both researchers and practitioners in this sector but, at the same time, large scale commercial applications have yet to be developed. This review, after briefly addressing the major challenges of the digital marketing ecosystem and the fundamental components of blockchain technologies, critically reviews academic works published the last 5 years in this field and highlights the current status, research topics and frameworks suggested. Moreover, the review addresses the main barriers to implementation of blockchain to large scale adoption in the digital marketing and advertising sector